Substantiation of principles of combined stage treatment of patients with colon cancer with unresectable liver metastases - K. H. Link; N. A. Maistrenko; Q. S. Tao; M. Kornmann; L. Staib; Ch. Link; J.-T. Li; S. Y. Peng; Z. L. Ji; M. Roitman; H. G. Beger (Вестник хирургии имени И.И. Грекова)
The article presents the results of long-term clinical, molecular-biological and laboratory studies on combined poly-stage treatment of patients with colon cancer with liver metastases. The cytotoxicity of various chemotherapeutic agents for colorectal carcinoma in the lines of HT 29 and NMG 64/84 cells was studied by analysis of human colony-forming tumor (HTCA). In vitro studies on the suspension of tumor cells from remote liver metastases were carried out to determine the most effective chemotherapeutic agents for intra-arterial hepatic infusion (HAI). Individual choice of the scheme of systemic chemotherapy depends on the level of thymidylate synthetase (TS) in the tumor tissue. Long-term own clinical experience and analysis of world literature allow authors to state that stage resection of the liver (STR) in combination with regional (HAI) and systemic chemotherapy is the method of choice in the treatment of patients with colorectal cancer with unresectable liver metastases. In comparison with other treatment methods (ALPPS and TSH), STR has the least negative consequences and is beneficial from the tumor-biological point of view.